Impairment of circulating endothelial progenitors in Down syndrome - Costa Valerio; Sommese Linda; Casamassimi Amelia; Colicchio Roberta; Angelini Claudia; Marchesano Valentina; Milone Lara; Farzati Bartolomeo; Giovane Alfonso; Fiorito Carmela; Rienzo Monica; Picardi Marco; et al. (BMC, 2010)
Abstract Background Pathological angiogenesis represents a critical issue in the progression of many diseases. Down syndrome is postulated to be a systemic anti-angiogenesis disease model, possibly due to increased expression of anti-angiogenic regulators on chromosome 21. The aim of our study was to elucidate some features of circulating endothelial progenitor cells in the context of this syndrome. Methods Circulating endothelial progenitors of Down syndrome affected individuals were isolated, in vitro cultured and analyzed by confocal and transmission electron microscopy. ELISA was performed to measure SDF-1α plasma levels in Down syndrome and euploid individuals. Moreover, qRT-PCR was used to quantify expression levels of CXCL12 gene and of its receptor in progenitor cells. The functional impairment of Down progenitors was evaluated through their susceptibility to hydroperoxide-induced oxidative stress with BODIPY assay and the major vulnerability to the infection with human pathogens. The differential expression of crucial genes in Down progenitor cells was evaluated by microarray analysis. Results We detected a marked decrease of progenitors' number in young Down individuals compared to euploid, cell size increase and some major detrimental morphological changes. Moreover, Down syndrome patients also exhibited decreased SDF-1α plasma levels and their progenitors had a reduced expression of SDF-1α encoding gene and of its membrane receptor. We further demonstrated that their progenitor cells are more susceptible to hydroperoxide-induced oxidative stress and infection with Bartonella henselae. Further, we observed that most of the differentially expressed genes belong to angiogenesis, immune response and inflammation pathways, and that infected progenitors with trisomy 21 have a more pronounced perturbation of immune response genes than infected euploid cells. Conclusions Our data provide evidences for a reduced number and altered morphology of endothelial progenitor cells in Down syndrome, also showing the higher susceptibility to oxidative stress and to pathogen infection compared to euploid cells, thereby confirming the angiogenesis and immune response deficit observed in Down syndrome individuals.